Pattern of recurrence in patients with ruptured primary gastrointestinal stromal tumour - Hohenberger, Peter; Ronellenfitsch, Ulrich; Oladeji, O.; Pink, Daniel; Ströbel, Philipp; Wardelmann, Eva; Reichardt, Peter (The British journal of surgery, 2010)
This study assessed the outcomes of patients with a gastrointestinal stromal tumour (GIST) that ruptured before or during resection.The records of 23 patients (8 women, 15 men; median age 54 years) with ruptured primary non-metastatic GIST were retrieved from a database of 554 patients. The written surgical and pathology reports were analysed. Review pathology was performed in all 23 cases, and mutational analysis of KIT and platelet-derived growth factor α (PDGFRA) genes was performed in 21 patients. Median follow-up was 52 months.Tumour rupture was spontaneous in 16 patients, following abdominal trauma in two and occurred during resection in five. Primary tumour location was the stomach in six patients, duodenum in one and small bowel in 16. Mean tumour size was 10·2 (range 4-28) cm. According to the Miettinen and Lasota risk classification, the distribution of very low-, low-, intermediate- and high-risk cases was one, two, five and 15 respectively. One patient remained disease-free at 83 months. Fifteen of 16 patients who did not receive adjuvant therapy developed tumour recurrence after a median of 19 months. Median recurrence-free survival in patients with KIT mutations involving codons 557-558 was 11 months.Patients with a rupture of GIST into the abdominal cavity have a risk of recurrence of nearly 100 per cent. In patients with deletion mutations involving codons 557-558, recurrence-free survival was less than 1 year. All patient groups are clear candidates for adjuvant drug therapy.
Published: 20 August 2010
Gesehen am 14.03.2023